Cultural Harmonization in the Midst of Modernity: A Sociological Study of the Mappacci Tradition in Bugis Weddings in Purun Village, Penukal District, Penukal Abab Lematang Ilir Regency (PALI) South Sumatra - Rantau Ismail (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2023)
Mappacci tradition in the community of Purun Village, Penukal Sub-district is an integral part of social and cultural life that forms identity and togetherness in the community. In a sociological review, this tradition offers valuable insights into social dynamics, social structures, and social interactions in the context of marriage and Bugis family life living in South Sumatra. This article outlines the sociological aspects of the Mappacci tradition, including cultural symbolism, cultural reproduction, social structure and social conflict. First, the analysis of cultural symbolism in Mappacci reveals how symbols such as pacci leaves, pillows and silk sarongs not only have individual meanings, but also illustrate the values, norms and social structures inherent in Bugis society. Secondly, the role of this tradition in cultural reproduction illustrates how marriage practices and the Mappacci ritual help maintain cultural identity and social solidarity within the community of Purun Village, Penukal Sub-district from generation to generation. Furthermore, an analysis of the social structure of Mappacci highlights the importance of family hierarchy, defined social roles, and gender norms in shaping the wedding procession and the implementation of the tradition. Finally, a review of social conflicts identifies potential tensions between customary traditions and modern values, as well as efforts to maintain the relevance of the Mappacci tradition in the face of evolving social dynamics. With these sociological aspects in mind, this article aims to provide a deeper understanding of the role and significance of the Mappacci tradition in the context of Bugis social and cultural life. In addition, the article also underscores the importance of sustaining and preserving cultural traditions to ensure the continuity of a rich cultural identity amidst the ever-changing currents of modernization and globalization.